Globally asynchronous sulphur isotope signals require re-definition of the Great Oxidation Event - Philippot, P.; Ávila, J.; Killingsworth, B.; Tessalina, Svetlana; Baton, F.; Caquineau, T.; Muller, E.; Pecoits, E.; Cartigny, P.; Lalonde, S.; Ireland, T.; Thomazo, C.; et al. (Macmillan Publishers Limited, 2018)
© 2018 The Author(s). The Great Oxidation Event (GOE) has been defined as the time interval when sufficient atmospheric oxygen accumulated to prevent the generation and preservation of mass-independent fractionation of sulphur isotopes (MIF-S) in sedimentary rocks. Existing correlations suggest that the GOE was rapid and globally synchronous. Here we apply sulphur isotope analysis of diagenetic sulphides combined with U-Pb and Re-Os geochronology to document the sulphur cycle evolution in Western Australia spanning the GOE. Our data indicate that, from ~2.45 Gyr to beyond 2.31 Gyr, MIF-S was preserved in sulphides punctuated by several episodes of MIF-S disappearance. These results establish the MIF-S record as asynchronous between South Africa, North America and Australia, argue for regional-scale modulation of MIF-S memory effects due to oxidative weathering after the onset of the GOE, and suggest that the current paradigm of placing the GOE at 2.33-2.32 Ga based on the last occurrence of MIF-S in South Africa should be re-evaluated.